OPTIMALISASI PERAN GURU PAI TERHADAP HASIL BELAJAR SISWA MASA PANDEMI COVID-19 - Fuji Pratami; Syamsiah Depalina Siregar (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2020)
The purpose of this study is to provide an overview of the optimization of the role of Islamic Education teachers as teachers and evaluators of student learning outcomes during the Covid-19 pandemic at SMA Negeri 1 Payakumbuh, and to provide an understanding of the importance of the role of PAI teachers as teachers and evaluators of student learning outcomes at the time. the Covid-19 pandemic at Payakumbuh 1 High School. Using field research (field research). Collecting data by observation, interviews and documentation. Using a qualitative descriptive approach. The main informants are 4 PAI teachers at SMA Negeri 1 Payakumbuh and the supporting informants are a list of the learning outcomes of the Odd PTS for the 2020/2021 academic year. The results of this study are the role of PAI teachers as teachers and evaluators of student learning outcomes during the Covid-19 pandemic at SMA Negeri 1 Payakumbuh being applied in the following ways: 1. The teacher and the school try to maximize the existence of alumni to procure mobile phones (HP) for online learning. 2. The teacher seeks face-to-face learning with limited time for students who have poor internet coverage for online learning. 3. The teacher implements online learning for students who have information communication technology devices and internet networks through the Zoom application, Google Class Room and Whatsaap. 4. After the teacher carries out his role as a teacher during the Covid-19 pandemic, student learning outcomes are obtained in the PAI-BP Subject with scores above the KKM.